Penggunaan Modifikasi Permainan Bola Voli Untuk Meningkatkan Kemampuan Passing Bawah Pada Peserta Didik SMAN 11 Semarang - Khoirunnisa, Arista; Setyawan, Danang Aji; Siswanto, Heri (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2025)
This research aims to determine the use of learning to play 3 on 3 on the results of volleyball bottom passing skills in Class XI students of SMA Negeri 11 Semarang. The research contains the impact of the training method with 3 on 3 games on bottom passing skills. A pretest-posttest design involving one group was used for this study.  The research population consisted of 35 students involved in Class XI of SMA Negeri 11 Semarang. The sampling technique applied is purposive sampling, which is taken from the lowest average pjok results in class XI. This study uses the test as an instrument, especially the lower pass test (Brumbach Forearm Pass Wall Volley Test). Normality tests, homogeneity tests, and hypothesis tests are some of the analyses used in the research. The volleyball bottom passing skill based on the comparison of the calculated t value obtained a score of 7,562 greater with a t-value of 2,030. Based on the results of the research that has been carried out, the use of 3 on 3 game modification media in learning football under passing material can provide an improvement in student learning outcomes, with a high level of completeness. For other researchers, it is also hoped that they will be able to conduct further research using materials outside of voleyball learning.